A Heptaplex PCR Assay for Molecular Traceability of Species Origin With High Efficiency and Practicality in Both Raw and Heat Processing Meat Materials - Zhou, Song; Zhong, Guowei; Zhou, Hanxiao; Zhang, Xiaoxia; Zeng, Xiaoqun; Wu, Zhen; Pan, Daodong; He, Jun; Cai, Zhendong; Liu, Qianqian (Frontiers in Nutrition, 2022)
Frequent meat frauds have become a global issue because adulteration risks the food safety, breaches market rules and even threatens public health. Multiplex PCR is considered to be a simple, fast, and inexpensive technique that can be applied for identification of meat products in food industries. However relatively little is known about a multiplex PCR method authenticating seven animal species simultaneously in one reaction due to technological challenge. Through screening new species-specific primers and optimizing PCR system, a heptaplex PCR method was established, which could simultaneously detect seven meat ingredients of camel (128 bp), pigeon (157 bp), chicken (220 bp), duck (272 bp), horse (314 bp), beef (434 bp) and pork (502 bp) in a single tube reaction. DNA sequencing solidly validated that each set of primers specifically amplified target species from total DNA mixtures of seven meat species. The developed multiplex assay was stable and sensitive enough to detect 0.01-0.025 ng DNA from various meat treatments including raw, boiled and autoclaved meat samples or target meat content of 0.1% total meat weight, suggesting the suitability of the heptaplex PCR technique for tracing target meats with high-accuracy and precision. Most importantly, a market survey validated the availability of this multiplex PCR technique in real-world meat products with a good application foreground.